2020
DOI: 10.1155/2020/6206157
|View full text |Cite|
|
Sign up to set email alerts
|

Cell Cycle Genes Are Potential Diagnostic and Prognostic Biomarkers in Hepatocellular Carcinoma

Abstract: Background. The cell cycle pathway genes are comprised of 113 members which are critical to the maintenance of cell cycle and survival of tumor cells. This study was performed to investigate the diagnostic and prognostic values of cell cycle gene expression in hepatocellular carcinoma (HCC) patients. Methods. Clinical features and cell cycle pathway gene expression data were obtained from the Gene Expression Omnibus and The Cancer Genome Atlas databases. Differentially expressed genes (DEGs) were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…( 30 , 31 , 32 ) More specifically, the loss of MAD1 function in HCC results in loss of mitotic checkpoint control and is associated with recurrence following surgical resection and decreased overall survival. ( 31 , 32 , 33 , 34 , 35 ) Several of the pathways positively associated with PSMA expression have roles in the tumor microenvironment, including cytokine–cytokine receptor interaction, extracellular matrix–receptor interaction, and phosphoinositide 3‐kinase–AKT signaling. ( 36 ) These data suggest potential areas for future research into the mechanistic role of PSMA‐associated angiogenesis in HCC, which may include FGF14 and MAD1 genes as well as tumor microenvironmental and angiogenic signaling in the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…( 30 , 31 , 32 ) More specifically, the loss of MAD1 function in HCC results in loss of mitotic checkpoint control and is associated with recurrence following surgical resection and decreased overall survival. ( 31 , 32 , 33 , 34 , 35 ) Several of the pathways positively associated with PSMA expression have roles in the tumor microenvironment, including cytokine–cytokine receptor interaction, extracellular matrix–receptor interaction, and phosphoinositide 3‐kinase–AKT signaling. ( 36 ) These data suggest potential areas for future research into the mechanistic role of PSMA‐associated angiogenesis in HCC, which may include FGF14 and MAD1 genes as well as tumor microenvironmental and angiogenic signaling in the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the GO terms and KEGG pathway of prognosis-associated genes is of great importance to the identi cation of prognostic biomarkers and eventually novel therapeutic targets in HCC. For instance, given the high enrichment of risk genes in the cell cycle signalling pathway, cell cycle genes may become potential candidates for developing prognostic biomarkers or druggable targets in HCC [26].…”
Section: Discussionmentioning
confidence: 99%
“…HCC, which accounts for 75%–85% of all liver cancer cases, is the most common histological type of primary liver cancer. Liping et al (2020) analyzed a large number of HCC data from the GEO and TCGA database and found that Bub3 gene expression level was significantly related to mortality, and patients with a higher expression level of Bub3 gene were expected to have a poorer prognostic outcome. It is speculated that Bub3 is a negative prognostic biomarker for HCC patients.…”
Section: Oral Cancermentioning
confidence: 99%
“…Turner et al, (2010) HCC Bub3 gene expression level was significantly related to mortality. Liping et al (2020) The higher the level of Bub3, the worse the prognosis.…”
Section: Mukherjee Et Al (2015)mentioning
confidence: 99%